ҚИЗИЛҚУМ ЧЎЛИНИНГ ЖАНУБИ-ҒАРБИЙ ҚИСМИ БИОХИЛМА- ХИЛЛИГИНИ МУҲОФАЗА ҚИЛИШДА БУХОРО ИХТИСОСЛАШТИРИЛГАН "ЖАЙРОН" ПитомнигиНИНГ ЎРНИ - Rahmonov, Nurali (Центр Научных Публикаций (buxdu.uz), 2024)
This article provides analytical information on the creation of the "Zhairon"nursery, the dynamics of changes in the population of rare species bred in it and the role nursery in preserving the biodiversity of the South-Western part of the Kyzlkum desert.